1994
DOI: 10.1111/j.1748-5827.1994.tb03821.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiotherapy alone and surgery and radiotherapy on survival of dogs with nasal tumours

Abstract: The case records of 26 dogs with nasal tumours, treated either with radiation alone or surgery and radiation, were compared. One‐ and two‐year actuarial survival rates for 12 dogs treated with radiotherapy were 58 and 13 per cent, respectively, compared to 71 and 38 per cent, respectively, for 14 dogs which were treated with surgery before radiotherapy. Sixty‐seven per cent of the dogs treated with radiotherapy had recurrent clinical signs by 52 weeks compared to 36 per cent of the dogs treated with surgery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 7 publications
3
30
0
7
Order By: Relevance
“…While it is not possible to directly compare the outcomes of this study with those of others, account should be taken of the differences in treatment approach. Other studies that have examined hypofractionated radiotherapy have reported median survival times between 146 and 441 days, and 1‐ and 2‐year survival rates of 25–58% and 9–15%, respectively (Morris et al , Mellanby et al , Gieger et al , Yoon et al ). The difference between the current regimen and those of the previous reports was the way in which the treatment fields were planned.…”
Section: Discussionmentioning
confidence: 99%
“…While it is not possible to directly compare the outcomes of this study with those of others, account should be taken of the differences in treatment approach. Other studies that have examined hypofractionated radiotherapy have reported median survival times between 146 and 441 days, and 1‐ and 2‐year survival rates of 25–58% and 9–15%, respectively (Morris et al , Mellanby et al , Gieger et al , Yoon et al ). The difference between the current regimen and those of the previous reports was the way in which the treatment fields were planned.…”
Section: Discussionmentioning
confidence: 99%
“…The most common breed in this study was the Shetland sheepdog; dolichocephalic dogs accounted for 93.8% [2,5,6,11,[13][14][15]. In this study, both the mean and median age of tumor occurrence were 10 years, which was similar to those previously reported [2,3,9,11,[14][15][16]. Histologically, 82% of the tumors were carcinomas; this percentage was higher than that obtained in the previous reports [2,3,16].…”
Section: Discussionmentioning
confidence: 99%
“…A combination of surgery, radiation, and/or chemotherapy is a standard treatment modality for nasal tumors in dogs [5,7,10,14,16,19]. The choice of treatment greatly depends on the location and size of the tumors obtained using radiography.…”
mentioning
confidence: 99%
“…The primary treatment of most canine intranasal neoplasms is radiotherapy (Lana et al 2004;Lawrence et al 2010) often with adjuvant chemotherapy (Lana et al 2004;Adams et al 2005). Neoadjuvant surgical debulking has also been described, but has not been shown to improve clinical outcome (Morris et al 1994;Adams et al 2005). Most intranasal cancers in humans are squamous cell carcinomas (Peryaga et al 2016).…”
Section: Introductionmentioning
confidence: 99%